Software Defect Elimination Information System in Software House Company - Johannes Simatupang (Jurnal Indonesia Sosial Teknologi, 2024)
In software that is free from defects or errors, a fixed method and technique of software testing is required. For this step, an Information System is needed to help eliminate software defects, so that testing or testing work is not a burden on software costs but is a perfection of software development work so that Zero Defect Application Software can be realized. From several software testing methods and techniques, a strategy suitable for the size of a software development project is required. So even though the software development project is small, it still requires a suitable test. And for software development testing to have reliable quality, it is necessary to measure and criteria for each software testing practice, so that a software development project can be determined in quality. To support software testing work, an Information System is needed that supports the need for processors to assess a quality software development test. With the Software Defect Elimination Information System, an objective quality of software development testing can be produced.